2015
DOI: 10.1111/pme.12840
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain, Comorbid Medical Conditions, and Associated Risk Factors in Kuwait: Gender and Nationality Differences

Abstract: This extensive survey study that found female Kuwaitis to have a higher incidence of pain and medical comorbidities than males and non-Kuwaitis highlights the role of cultural factors in contributing to pain and comorbid medical conditions. This information is critical in organizing resources to implement adequate healthcare services and behavioral interventions in Kuwait and other Arab countries to improve pain and health-related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
7
2
Order By: Relevance
“…The findings of this study and others10,13,37,39 suggest that very few individuals in Kuwait take prescription medication to manage their pain, including muscle relaxants, anticonvulsants, tranquilizers, antidepressants, and opioids. Evidence-based recommendations from systematic literature reviews and existing guidelines have strongly supported the use of tri-cyclic antidepressants, serotonin–noradrenaline inhibitors, pregabalin, and gabapentin for treating pain with neuropathic characteristics 40.…”
Section: Discussionsupporting
confidence: 47%
“…The findings of this study and others10,13,37,39 suggest that very few individuals in Kuwait take prescription medication to manage their pain, including muscle relaxants, anticonvulsants, tranquilizers, antidepressants, and opioids. Evidence-based recommendations from systematic literature reviews and existing guidelines have strongly supported the use of tri-cyclic antidepressants, serotonin–noradrenaline inhibitors, pregabalin, and gabapentin for treating pain with neuropathic characteristics 40.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, females usually live longer than males; hence, the difference increases with aging. In this respect, this study did not find any differences in the prevalence of chronic pain based on sex, suggesting that regional and cultural differences may need to be considered when the relationship between sex and chronic pain be examined [39,40].…”
Section: Discussionmentioning
confidence: 57%
“…A recent survey conducted in Kuwait found that females have a higher incidence of CP as compared to males and non-Kuwaitis [30]. A review conducted recently indicated an escalation in the prevalence of back pain in the Arab world [31].…”
Section: Introductionmentioning
confidence: 99%